Pervasive Computing - Indulska, J. (Springer, 2017)
The 18 revised full papers presented were carefully selected during two rounds of reviewing and improvement. The papers are organized in topical sections on sensing and activity recognition, applications for mobile devices, location in pervasive systems, platforms for pervasive computing, lessons learned from displays, games and health applications, as well as privacy and security.